Beginning Blender - Flavell, Lance (Apress, 2012)
Welcome to the world of 3D! The fact that you are reading this book means that there is a good chance you are interested in 3D animation. You have heard that Blender is a freely available program capable of making such animations, so now you want to know how to use it, and fast! But then, it’s dangerous for me to guess this scenario. Perhaps it’s 3D games you’re interested in making. Perhaps you’re not into the animation side of things, but you want a good reference on how to get started on making your own 3D models. Maybe you’ve heard that Blender has some powerful video-editing capabilities. Well, Blender can do all these things and so much more. When I started using Blender, I was soon overwhelmed with the many controls it has. Buttons just seemed to be arranged all over the place! When I pressed one button to see what it did, sometimes all the other controls around it would change, but I had no clue as to what the button I had just clicked was supposed to be doing.